Neoliberalism can reduce well‐being by promoting a sense of social disconnection, competition, and loneliness - Becker, Julia C.; Hartwich, Lea; Haslam, S. Alexander (British journal of social psychology, 2021)
Neoliberalism has become the dominant ideology in many parts of the world. Yet there is little empirical research on its psychological impact. On the basis of a social identity approach to health, we hypothesize that, by increasing competition and by reducing people’s sense of connection to others, neoliberalism can increase loneliness and compromise our well‐being. Study 1 (N = 246) shows that the more neoliberal people perceive society to be, the worse their well‐being, and that this relationship is mediated via loneliness. In two experiments, we showed that exposure to neoliberal ideology increases loneliness (Study 2, N = 204) and, through this, decreases well‐being (Study 3, N = 173). In Study 4 (N = 303), we found that exposure to neoliberal ideology increased loneliness and decreased well‐being by reducing people’s sense of connection to others and by increasing perceptions of being in competition with others. In Study 4, the effect of neoliberalism on well‐being was evident for liberals only. We discuss the potential impact of neoliberalism on different social groups in society.